A case of progressive non-fluent aphasia as onset of amyotrophic lateral sclerosis with frontotemporal dementia. (3rd July 2019) - De Marchi, F.; Tondo, G.; Sarnelli, M.F.; Corrado, L.; Solara, V.; D'Alfonso, S.; Cantello, R.; Mazzini, L.
Abstract: The association between Amyotrophic Lateral Sclerosis (ASL) and FrontoTemporal Dementia (FTD) is well known. Most of reports describing ASL-FTD cases show a strong association between ALS and the behavioural form of FTD. Conversely, the association between ALS and pure Semantic Dementia or Progressive Non-Fluent Aphasia (PNFA) is extremely rare, ranging from 1 to 3%. A clinical phenotype characterized by a rapidly progressive aphasic dementia and motoneuron disease (MND) has been described in few case reports; since the updating of PNFA diagnostic criteria in 2011, no clinical report has been related. We want to describe a case of patient presented, at the onset, as PNFA who developed, one year later, ALS with bulbar onset. The patient was screened for the main genes causing or associated with MND and/or dementia but no variants with a pathogenetic effect were observed.